Strategi Pemasaran Air Minum dalam Kemasan pada Agen PT. Izauranet Berkah Mandiri - Alfiyatul ‘Izzah; Muhammad Alhada Fuadilah Habib (Universitas 45 Surabaya, 2024)
Marketing strategy is a process that plays an important role in marketing goods and services to consumers because in this era competition is very tight so you need a good marketing strategy to win the competition in the business world. The purpose of this research is to find out what strategies are carried out by PT agents. iZaura in marketing its products to increase sales. This research uses a descriptive qualitative approach. The data obtained is the result of interviews, observation and documentation. The results of this research found that in increasing business sales, iZaura agents used the 7P marketing mix strategy. The 7P marketing mix strategy includes products that are marketed using good quality water that has been sterilized. Providing affordable prices, apart from having a strategic location and easy to reach, carrying out promotions using online or offline media, providing friendly service and having quality human resources, carrying out detailed production processes and multi- level marketing processes in stages, having Attractive purple packaging with the unique iZaura logo.